Analisis Pengelolaan Dana Desa Dalam Pembangunan Di Kampung Waena Distrik Heram Kota Jayapura Tahun 2019-2021 - Ester Rosalina Komboy; Transna Putra Urip; Sarlota A. Ratang (Universitas Cenderawasih, 2022)
The study's objectives are as follows: 1) to determine the level of village fund management in Waena Village from 2019 to 2021. 2) To find out the achievements of the village fund management and also find out the challenges and obstacles faced by the Waena village government in realizing the village funds for the welfare of the Waena village community. The types of research used are quantitative and qualitative, and the data collection techniques used are observation, documentation, literature study, interviews, and questionnaires. However, the effectiveness ratio and qualitative descriptive analysis are also used in the form of exposure to the results of interviews and questionnaires. The results of this study indicate that: 1) The realization of village funds is estimated together with the 2019 target of reaching 91% or